Evaluation and Improvement of Telephony Call Center Business Process at An Indonesian Bank - Ravindra, Farrel (Proceedings International Conference on Education Innovation and Social Science, 2023)
This research focuses on the problem of uneven queuing distribution among call center agents at PT. BXX, revealing flaws in the organization's current business process. Business process reengineering (BPR) is employed, involving service blueprint mapping, analysis, and the development of a new process to rectify this issue. The data collection process incorporates various sources such as company reports, observations, and interviews with the call center manager. The analysis reveals 14 necessary but non-value-added activities and 8 value added activities within the current business process. A potential fail point is identified where instances of the product owner failing to fulfill the caller's request within the expected time resulting in repeat calls. Repeat callers are required by the company to be assigned to the previous agent they interacted with to save time. However, this can lead to the accumulation of long queues for certain agents, resulting in increased average waiting time and a higher likelihood of abandonment. The proposed to-be business process suggests incorporating a progress update process and modifying the queuing process to include a callback option. These solutions aim to reduce repeat calls, inform callers about their requests, and prevent queue buildup. Expected outcomes are improved queuing distribution, reduced wait times, and decreased call abandonment. This research contributes to the business process management field by using BPR to address uneven queuing in BXX's call center. Findings provide guidance to organizations facing similar challenges, offering insights into enhancing efficiency and customer service through business process reengineering.